We need better understanding about functional diversity and vulnerability of tropical freshwater fishes - Vitule, Jean R. S.; Agostinho, Angelo A.; Azevedo-Santos, Valter M.; Daga, Vanessa S.; Darwall, William R. T.; Fitzgerald, Daniel B.; Frehse, Fabrício A.; Hoeinghaus, David J.; Lima-Junior, Dilermando P.; Magalhães, André L. B.; Orsi, Mário L.; Padial, André A.; et al. (Biodiversity and conservation, 2017)
Here we extend a discussion initiated by Toussaint et al. (Sci Rep 6:22125, 2016 ) concerning the relationship between global patterns of freshwater fish functional diversity (FD) and its vulnerability to human impacts. Based on a set of morphological traits, they concluded that Neotropical freshwater fishes have highest FD, but low vulnerability given high levels of functional redundancy. This conclusion implies that conservation efforts for freshwater fishes should emphasize temperate regions. This perspective is risky, because Toussaint et al.’s study seriously underestimates the full scope of FD, including important ecosystem services provided by fishes in the tropics. We briefly discuss some additional and well-documented aspects of tropical freshwater fish FD and conclude that tropical fish FD is highly vulnerable.